2010
DOI: 10.1185/03007991003658956
|View full text |Cite
|
Sign up to set email alerts
|

Burden of schizophrenia in recently diagnosed patients: healthcare utilisation and cost perspective

Abstract: Only commercially insured patients and direct medical costs were included, therefore, results may underestimate the economic burden of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 42 publications
2
57
0
3
Order By: Relevance
“…Inpatient care represents the primary driver of costs associated with schizophrenia, accounting for between one-third and two-thirds of the total direct health care costs of patients with schizophrenia [3-6]. Indeed, most of these patients will experience a chronic course with many relapses, characterized by an exacerbation of psychosis, emergency room (ER) visits, and rehospitalizations [7-9].…”
Section: Introductionmentioning
confidence: 99%
“…Inpatient care represents the primary driver of costs associated with schizophrenia, accounting for between one-third and two-thirds of the total direct health care costs of patients with schizophrenia [3-6]. Indeed, most of these patients will experience a chronic course with many relapses, characterized by an exacerbation of psychosis, emergency room (ER) visits, and rehospitalizations [7-9].…”
Section: Introductionmentioning
confidence: 99%
“…The annual frequencies of relapses requiring hospitalization and relapses not requiring hospitalization were obtained from a 2010 US burden of illness article by Nicholl et al 35 , which reported the mean number of psychiatric hospitalizations and ER visits per patient with schizophrenia per year (Table 1). …”
Section: Relapse Frequency and Durationmentioning
confidence: 99%
“…Enhancing patients’ cognition will not only improve their quality of life, but will also enable them to access jobs and integrate with society. In consequence, governments are relieved from the cost burden of ongoing care for these patients (Nicholl et al 2010). In keeping with this, we have shown that PCE drugs improve cognitive performance in patients with schizophrenia (Barnett et al 2010), and that modafinil (Provigil®), a wake-promoting drug licensed for narcolepsy, can improve cognitive flexibility as measured by extra-dimensional attentional set-shifting in patients with chronic schizophrenia (Turner et al 2004 a ).…”
Section: Pharmacological Cognitive Enhancers (Pces)mentioning
confidence: 99%